2007
DOI: 10.1310/tsr1401-98
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Driving Ability Following Stroke: A Systematic Review

Abstract: Cognitive tests that assess multiple cognitive domains relevant to driving appear to have the best reproducibility in predicting fitness to drive in stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(138 citation statements)
references
References 35 publications
5
127
1
5
Order By: Relevance
“…In laboratory settings with the use of simulators, the age of drivers influenced DRT 17,18) . Elderly drivers react more slowly than younger drivers because it is more difficult for older people to properly judge traffic environments and to stop initiated movements.…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory settings with the use of simulators, the age of drivers influenced DRT 17,18) . Elderly drivers react more slowly than younger drivers because it is more difficult for older people to properly judge traffic environments and to stop initiated movements.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier review of 17 studies that examined predictors of driving ability post-stroke found that cognitive ability was the most useful screening test (12). We used multivariate analysis to identify predictors of track test performance from the results of neuropsychological tests.…”
Section: Driving Simulatormentioning
confidence: 99%
“…A road test is generally considered to be the gold standard for evaluation of driving ability (12); however, several facilities in Japan use a track test. Regardless of the setting, evaluation of driving ability requires resources for both patient and the driving school.…”
Section: █ Conclusionmentioning
confidence: 99%
“…For example, researchers have found the Trails B to be a valid predictor of on-road performance in 127 community-dwelling older licensed drivers (Classen et al, 2008) and in people with Parkinson's disease (Classen et al, 2011;Uc et al, 2006). Others (Marshall et al, 2007;Novack et al, 2006) have found the Trails B to be a valid predictor of driving performance in patients with brain injury or predictive of simulated driving performance in older adults (Mullen, Weaver, Riendeau, Morrison, & Bédard, 2010).…”
Section: Trails B and On-road Studiesmentioning
confidence: 99%